Faktor penggunaan tenaga elektrik yang tinggi di kolej kediaman Universiti Teknologi Malaysia - Jaaffar, Zulhairi (2014)
Growth of energy demand continued to increase every year. The sudden increase in energy usage was requiring government actions from the aspect of energy efficiency by ensuring minimize wastage. The term energy refers to specifically electricity. Residential buildings are important contributors to energy consumption from total energy usage. Although many initiatives have been implemented to improve the energy efficiency of building, there are some obstacles like unclear and inconsistent data on the factors leading to the high energy consumption in this sector. This study is related to the consumption of electricity in UTM’s residential colleges. There are two objectives of this study, first is to identify the factors influence energy usage in the UTM’s residential colleges. Second objective is to determine the critical factor that lead to high electricity usage in UTM’s residential colleges. The research methodology consisted of literature review, data collection and data analysis. The data were obtained through questionnaires given to eleven residential colleges management in UTM and maintenance staffs. Descriptive analysis using SPSS software which involved frequency and critical index calculation are used in this study. These finding have identified factors that influenced building’s energy consumption are non design factor and passive design factor. Whilst residential behaviour and contruction detailing are the critical factors that lead to high energy usage in UTM’s colleges. The findings of this study can provide relevant information to the management of colleges in planning and implementation of effective and efficient activities in dealing with high electricity usage.